Custumer Satisfation Based on Quality Product and Brand Image - Syita Oktaviani Zuniarti; Dwi Gemina; Chandra Ayu (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In the era of globalization, the beverage packaging industry has experienced rapid growth, including intense competition in the tea beverage sector. This study aims to analyze the effect of product quality and brand image on consumer satisfaction of tea beverage X PT. TFJ, both simultaneously and partially. The research sample consisted of 100 consumers who had purchased the product more than twice, selected using purposive sampling techniques. The research instrument was tested for validity, reliability, and classical assumption tests. The analysis method used was a descriptive and verification approach with multiple linear regression. The results showed that product quality and brand image had a positive and significant effect on consumer satisfaction, both together and individually. Brand image had the most dominant effect on consumer satisfaction compared to product quality. These findings indicate that brand image improvement strategies should be a priority for companies in maintaining customer satisfaction. In addition, improving product quality is still needed to strengthen competitiveness in the competitive tea beverage industry.